2017
DOI: 10.1200/jco.2016.70.8297.2017.2.test
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti-Trop-2 Antibody Drug Conjugate Sacituzumab Govitecan (IMMU-132) in Heavily Pretreated Patients With Metastatic Triple-Negative Breast Cancer

Abstract: Author affiliations and support information (if applicable) appear at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 37 publications
8
99
0
1
Order By: Relevance
“…In particular, the same conjugation method has been used to create an anti-Trop-2 SN-38-ADC (sacituzumab govitecan, IMMU-132) that targets Trop-2 on solid tumors, and likewise has been shown to be superior to parental antibody both in vitro and in vivo (18,19,31). Further, it has demonstrated efficacy in heavily pretreated metastatic triple-negative breast cancer, as well as small-cell and non-small-cell lung cancer patients (14)(15)(16), suggesting that IMMU-140 may prove to be superior to its parental antibody clinically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the same conjugation method has been used to create an anti-Trop-2 SN-38-ADC (sacituzumab govitecan, IMMU-132) that targets Trop-2 on solid tumors, and likewise has been shown to be superior to parental antibody both in vitro and in vivo (18,19,31). Further, it has demonstrated efficacy in heavily pretreated metastatic triple-negative breast cancer, as well as small-cell and non-small-cell lung cancer patients (14)(15)(16), suggesting that IMMU-140 may prove to be superior to its parental antibody clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The moderately stable linker in these unconventional ADCs enables the drug to be released in the acidic pH of tumor microenvironment, while internalization further increases the drug's bioavailability. These design features, while not amenable to showing specificity in vitro, have resulted in encouraging clinical activity of other ADCs (anti-Trop-2 ADC, anti-CEACAM5 ADC) in solid cancer therapies (14)(15)(16)(17)30). In particular, the same conjugation method has been used to create an anti-Trop-2 SN-38-ADC (sacituzumab govitecan, IMMU-132) that targets Trop-2 on solid tumors, and likewise has been shown to be superior to parental antibody both in vitro and in vivo (18,19,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNBC represents only 15-20% of patients with breast cancer. TNBC poor prognosis may be due to its unique histological features such as high grade, high proliferative rate, low apoptotic cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, three clinical trials reported in the American Society of Clinical Oncology (ASCO) meeting of 2016 using new targeted therapies have presented the successful results of against triple negative breast cancer. These studies target to Trop2 [9], frizzled receptor and PD-L1 [10,11] oncoproteins in combination with the chemotherapy paclitaxel exhibit great potential to extend the lives of TNBC patients whose cancers have progressed after previous treatments. However, intense research is still carrying on to identify specific biomarkers and develop additional and effective treatment options.…”
Section: Introductionmentioning
confidence: 99%